Impregnation Effect of Synthesized Fe3O4 Nanoparticles on the Jabon Wood’s Physical Properties - Rahayu, Istie Sekartining; Ismail, Rohmat; Darmawan, Wayan; Wahyuningtyas, Irma; Prihatini, Esti; Laksono, Gilang Dwi; Khairunissa, Dhiya (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study focused on characterizing synthetic magnetite (Fe3O4-NP) and evaluating the impregnated jabon wood’s physical properties. The co-precipitation method used for the synthesis of Fe3O4-NP, namely by mixing the iron solution (n/n Fe2+:Fe3+=1:2) with the strong base of sodium hydroxide (NaOH) (MG-S) and weak base of ammonium hydroxide (NH4OH) (MG-W) as precursors. The impregnation stage uses parameters of a -0.5 bar vacuum for half an hour and 2 bar pressure for 2 hours with magnetite concentrations of 1; 2.5; 5% w/v in a demineralized water solvent. Scanning electron microscopy-energy dispersive x-ray spectroscopy (SEM-EDX) and Fourier transform infrared spectrometry (FTIR) confirmed the presence of Ferrum content and Fe-O functional group in both Fe3O4-NPs produced. The Fe3O4-NP size was also measured via the X-ray diffraction analysis, namely 34.54 nm for the MG-S and 39.24 nm for the MG-W. Magnetic strength obtained was 7.51 mT for the MG-S and 8.58 mT for the MG-W. The impregnated jabon wood’s physical properties also improved with indications of an increase in wood density, weight percent gain (WPG), bulking effect (BE), anti-swelling efficiency (ASE), and a decrease in water absorption (WA). The results showed the best treatments were MG-S 2.5% and MG-W 5%.